2015
DOI: 10.1111/obes.12120
|View full text |Cite
|
Sign up to set email alerts
|

To What Extent Does the Interest Burden Affect Firm Survival? Evidence from a Panel of UK Firms during the Recent Financial Crisis

Abstract: Using a panel of mainly unquoted UK firms over the period 2000-09, we document a significant effect of changes in the interest burden from debt-servicing on firm survival. The effect is found to be stronger during the recent financial crisis compared with more tranquil periods. Furthermore, the survival chances of bank-dependent, younger, and nonexporting firms are most affected by changes in the interest burden, especially during the crisis. Our results are robust to using different estimation methods and dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 47 publications
5
29
0
Order By: Relevance
“…Bridges and Guariglia (2008) studied UK firms from 1997-2002 to determine that higher leverage leads to a higher probability of failure; however, such an effect is more pronounced for domestic firms but somewhat mitigated for globally engaged firms. Guariglia et al (2016) confirmed the earlier finding using UK data but for a different period; they maintained that an economic crisis tended to hit bank-dependent and non-exporting firms hard through higher interest rates. This channel of interest rates during a financial crisis was echoed by Boeri et al (2013), who stated that firms that have borrowed more experience larger layoffs, and by Byrne et al (2016), who emphasized that bank-dependent nonpublic firms end up with higher rates of failure due to increased uncertainty.…”
Section: Literature Reviewsupporting
confidence: 85%
“…Bridges and Guariglia (2008) studied UK firms from 1997-2002 to determine that higher leverage leads to a higher probability of failure; however, such an effect is more pronounced for domestic firms but somewhat mitigated for globally engaged firms. Guariglia et al (2016) confirmed the earlier finding using UK data but for a different period; they maintained that an economic crisis tended to hit bank-dependent and non-exporting firms hard through higher interest rates. This channel of interest rates during a financial crisis was echoed by Boeri et al (2013), who stated that firms that have borrowed more experience larger layoffs, and by Byrne et al (2016), who emphasized that bank-dependent nonpublic firms end up with higher rates of failure due to increased uncertainty.…”
Section: Literature Reviewsupporting
confidence: 85%
“…Given that the European-wide monetary policy hardly will adapt to the domestic situation of peripheral countries (as Spain or eventually Romania) real convergence must be achieved before becoming member of EMU; otherwise the European monetary policy (adapted to the core of the EMU) can be devastating for the productive sector of those countries which experience a different situation from those ones that justify the adopted monetary policies. The influence of interest rates over the firms' situation, till the point of affecting its solvency is one of the most common results that previous research has found and it must be stressed that microeconomic analyses (see, for example Guariglia et al (2016), for an analysis with a panel of UK firms in 2000-2009) confirm its importance. Moreover, ISR responds negatively to RT shocks both in the case of Romania and in the case of Spain, their effects being statistically significant during the first 7 and 3 quarters, respectively.…”
Section: Discussionmentioning
confidence: 95%
“…The ability to access external funds should also have a positive impact on firm growth and survival (Musso and Schiavo, 2008). Even though stock markets in CEE countries have various specific characteristics (as emerging markets), solvency as a ratio of share shareholders' funds to total assets should be positively associated with firm survival (as recently found by, e.g., Guariglia et al, 2016). The recent financial crisis influenced listed and bond-issuing firms roughly by reducing their capital (Iwasaki, 2014), and, as found by Guariglia et al (2016), during and after the crisis, chances of survival for bank-dependent, younger, and non-exporting firms are most affected by changes in the interest burden.…”
Section: Firm-specific Factorsmentioning
confidence: 87%